Time-varying hedging using the state-space model in the Malaysian equity market - Izani Ibrahim,; Sheela Devi D. Sundarasen, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Theoretical and practice of financial hedging have expanded over the last 25 years. Research in this area is numerous and one of them is identifying the time-varying optimal hedge ratio. In this study, the time-varying hedge ratio is analysed using the State Space model (Kalman Filter) on daily Kuala Lumpur Composite Index (KLCI) and Kuala Lumpur Future Index (KLFI) from April 2005 to March 2008. Comparison between the static and time-varying hedge ratio and forecast performance is done to analyse the efficiency of the time-varying estimates. Our results show that for forecasting purposes the State Space model has the ability to forecast better when 30 days of forecast horizon are used. The volatility of the time varying hedge ratio is relatively low, but the static estimate of the hedge ratio overestimates the amount of the KLFI futures contract needed to hedge the KLCI. This may prove to be an unnecessary cost for fund managers in hedging using KLFI